Vehicle to vehicle data transfer and communication using LI-FI technology. (2021) - Anbalagan, R.; Hussain, M. Zahir; Jayabalakrishnan, D.; Naga Muruga, D.B.; Prabhahar, M.
Abstract: The concept of Vehicle to vehicle data transmission refers to the communication between two vehicles that ensures safety and security of the vehicle occupants. In this project, we present the designs and results of a prototype using the light fidelity (Li-Fi) technology, which is the latest technology that was developed in the last few years, which needs some systematic inquiry on its sustainability for use in the vehicles. Vehicle to vehicle communication is the most effective solution that is available in order to reduce the road accidents. The proposed use of this Li-Fi technology comprises mainly the light- emitting diode (LED) bulbs as the means of connectivity that functions by sending data through the light spectrum as an optical wireless medium for the signal propagation. In fact, the usage of these light emitting diode (LED) eliminates the need of a complex wireless networks and protocols. The designed system ensures a highly-reliable communication between the vehicles so that accidents can be reduced to a greater extent.